REDENTIAL - Ms Ramya R, Veeerapandi S, Janarthanan S, Josiah Devasam Hanana J (International Journal of Advanced Science and Technology, 2020)
Certification, provided in the organizations or institutions are the proof for the completion of the course. It states that a person holding the certificate is having the knowledge on the certificate provided area and capable of doing work in those areas. With this approach a certificate is developed using blockchain technology. In this, there are three types of users namely Certificate Issuer(Institudes), Recipient(Student), Verifier(Employer). The Issuer will issue the certificate in the blockchain network and Employers who want to verify the certificate can verify it.